2015
DOI: 10.1177/0269216314560007
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care in the intensive care unit: A patient-based questionnaire of intensive care unit staff perception and relatives’ psychological response

Abstract: Background: Communication is a hallmark of end-of-life care in the intensive care unit. It may influence the impact of end-of-life care on patients’ relatives. We aimed to assess end-of-life care and communication from the perspective of intensive care unit staff and relate it to relatives’ psychological symptoms. Design: Prospective observational study based on consecutive patients with severe sepsis receiving end-of-life care; trial registration NCT01247792. Setting/participants: Four interdisciplinary inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 41 publications
3
41
2
6
Order By: Relevance
“…2CFurther research is needed to identify the most effective and cost-effective ways to implement routine family conferences in the ICU setting. Numerous observational studies have suggested the need for improved communication with family members (137,(162)(163)(164)(165)(166)(167). One multicenter observational study analyzed recordings of 51 family conferences and published results in a series of articles (151)(152)(153).…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…2CFurther research is needed to identify the most effective and cost-effective ways to implement routine family conferences in the ICU setting. Numerous observational studies have suggested the need for improved communication with family members (137,(162)(163)(164)(165)(166)(167). One multicenter observational study analyzed recordings of 51 family conferences and published results in a series of articles (151)(152)(153).…”
Section: Recommendationmentioning
confidence: 99%
“…Ample evidence exists describing the importance that patients and families place on high-quality communication in the ICU (26,27,170,171). Furthermore, additional evidence demonstrates that poor communication can cause patient and family dissatisfaction (162)(163)(164)(165) and even harm in the form of anxiety, depression, symptoms of PTSD and complicated grief (137,166,167,172). Given the importance of high-quality staff-family communication to familycentered outcomes, many investigators have examined communication training programs as an intervention to improve the quality of communication in the ICU setting.…”
Section: Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on experiences of FCs of palliative patients in hospitals provide useful information about the range of potential psychosocial problems and needs. For example, in intensive care units, a substantial proportion of FCs showed symptoms of post-traumatic stress disorder (51%), anxiety (48%) or depression (33%) [29]. A study comparing FCs’ burden and quality of life in active treatment settings and hospice care reported the hospice group to have significantly lower values in the observed emotional and mental domains [30].…”
Section: Introductionmentioning
confidence: 99%
“…Na prática, é frequentemente observada a deficiência na comunicação com familiares dos pacientes criticamente doentes, o que se associa à maior angústia da família (HARTOG et al, 2015). A comunicação entre os médicos e familiares também é usualmente rápida, fragmentada e com grandes riscos de falhas, por faltarem oportunidades para fornecimento de respostas empáticas às emoções da família, que carecem de tempo suficiente para expressar seus objetivos e preocupações (PESSINI e BERTACHINI, 2005), principalmente num contexto de pronto-atendimento, em que as intervenções de saúde exigem maior agilidade e resolutividade imediatas.…”
Section: Lista De Tabelasunclassified